Business math (New York, NY 3G E-Learning LLC, 2023)
Providing comprehensive coverage of personal and business-related mathematics, the book is refreshingly different in its approach, and endeavors to motivate student to learn the concept and apply them in real-life situations.
Section 1: Fundamental operations
Unit 1: Fractions, decimals and percentage

Section 2: Ratio and proportion
Unit 2: Overview of ratio and proportion

Section 3: Buying and selling
Unit 3: Overview of buying and selling
Unit 4: Sales forecasting

Section 4: Salary and wage
Unit 5: Operations of mathematics in salaries and wages

Section 5: Presentation and analysis of business data
Unit 6: Business data presentation in graphs, charts, and tables
Unit 7: Data collection
Unit 8: Rank and percentile
Includes bibliographical references (pages 172-173) and index
Keywords: Business mathematics